Analysis of Contents of the Indonesian Public Relations Textbook on Digital Public Relations - I Gusti Ngurah Putra (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Textbooks play an important role in the learning process in universities. They must be able to present the latest developments in theory, concepts and their application in everyday life. In the field of public relations, the existence of textbooks has been recorded since  public relations as a scientific discipline was taught in universities. Unfortunately, there is  almost no  research that examines public relations textbooks in Indonesia. Therefore, this research asks the question of  how does public relations textbook written by Indonesian authors discuss digital public relations? The research was conducted through a qualitative approach by describing the discussion of digital public relations and analyzing how public relations textbooks place digital communication technology in public relations. This study found that not all introductory public relations textbooks published between 2015-2020 presented a chapter on digital public relations. The introductory public relations textbooks analyzed presented various digital public relations topics.  However, only one textbook that discusses digital public relations is relatively adequate as an introduction.  There is a tendency to see digital media technology as a continuation of previous media technology.  Digital media has not been fully placed as a medium that allows the process of dialogue and sees media users as the public who can create, produce, modify and share messages through social networks. This research has only succeeded in identifying four textbooks so that the results of this research cannot be used to make generalizations about the discussion of digital public relations. Further research can be directed to study by comparing digital public relations discussions in English texts or translations with Indonesian textbooks.